Climate justice repercussions and implications - Mohamed, Sami ElTayeb Idris (Journal of Economic, Administrative and Legal Sciences, 2023)
This scientific study was titled Climate Justice, its Implications and Effects. It dealt with the concept and development of climate justice and its relationship to climate change, and international and national efforts to overcome its devastating effects. The study aimed to introduce climate justice, its causes, and its effects on environmental human rights. In order to reach scientific results, the study followed the descriptive analytical approach in addressing the issues and extrapolating the different legal texts. The study reached results, perhaps the most prominent of which is that climate justice is a modern term, and it is a mixture between human rights and climate changes, and aims primarily to protect enviromental human rights that are negatively affected by climate changes. The most important recommendations are the need to unite efforts between environmental law and human rights to ensure effective protection of the environment that overshadows the protection of enviromental human rights.